Municipal wastewater reclamation and water reuse for irrigation by membrane processes - Dolar, Davor (Array, 2019)
Municipal wastewater was treated by membrane bioreactor (MBR), and the obtained MBR effluent was then treated by reverse osmosis (RO), and nanofiltration (NF). The MBR effluent was additionally treated by reverse osmosis (XLE) and nanofiltration (NF90 and NF270) membranes. RO and NF permeate output streams were assessed for their utilization in agricultural irrigation. The MBR used a hollow fiber ZeeWeed 1 ultrafiltration membrane. Conductivity, turbidity, total suspended solids, chemical oxygen demand, and dissolved organic carbon were rejected by MBR with average values of 10 %, 100 %, 99.8 %, 96 %, and 88 %, respectively. Further treatment with RO/NF membranes showed additional reduction in all measured parameters. According to results, MBR effluent belongs to the ‘slight to moderate’ degree of restriction on use due to conductivity, chloride, and sodium concentrations. RO/NF permeate, based on all parameters, belongs to the ‘none’ degree of restriction on use, except on sodium adsorption ratio (SAR), where it belongs to the ‘severe’ degree of restriction on use. Based on conductivity and SAR parameters, assessment of produced water quality obtained by blending of two effluents (50 % of MBR and 50 % of NF270 permeate) resulted in an output stream appropriate for irrigation, proving that the blending of output streams in this ratio is a good strategy for agricultural irrigation.